Organic Matter Accumulation Mechanism in the Lower Cambrian Strata from Well Luntan 1 in the Tarim Basin, NW China - Qian Deng; Haizu Zhang; Haozhe Wang; Zhiwei Wei; Bin Cheng; Shida Li; Yunpeng Wang; Oluwabamise Lekan Faboya; Zewen Liao (Geofluids)
A large amount of light crude oils have been found within 4000 to 7000 m deep strata of Cambrian, Ordovician, and Silurian reservoirs in the Tarim Basin, NW China. To enhance the understanding of parental materials of deep oils, a set of high-quality source rocks from the Yuertusi Formation in well Luntan 1 (maximum drilling depth of 8882 m) was studied in terms of their sedimentary condition and mechanism of organic matter enrichment. Total organic carbon (TOC) content, carbon isotope of kerogen (δ13Cker), and major and trace elements of the rocks from the Sinian Qigebulake, Cambrian Yuertusi, and Xiaoerbulake Formations in well Luntan 1 were analysed. The results showed that the δ13Cker value of the Yuertusi Formation barely changed with an average of -31.19‰. High TOC contents accompanied by enrichments of the bioessential trace elements, such as cadmium, chromium, copper, nickel, and zinc, occurred in the lower part of the Yuertusi Formation. Excess barium (Baxs) and phosphorus concentrations revealed high primary productivity during the deposition of the Yuertusi Formation. Moreover, variations in the enrichment factors of molybdenum, uranium, and vanadium and molybdenum-uranium covariation pattern indicated suboxic-anoxic conditions in the Qigebulake Formation, anoxic-euxinic conditions in the Yuertusi Formation, and suboxic-oxic conditions in the Xiaoerbulake Formation. The TOC contents were significantly correlated with the paleoproductivity and paleoredox parameters, indicating that high productivity and reducing conditions jointly controlled the organic matter accumulation and preservation in well Luntan 1.